Quality Evaluation of the Tomato Paste Produced in the Libyan Arab Republic - DRAWILL, ABD-EL-MAGID E.; EL-GHARBAWI, MOHAMED I. (The Libyan Journal of Agriculture, 2023)
Five brands of tomato paste produced locally in the Libyan Arab Republic were physico-chemically analysed to evaluate their quality. Their properties were compared with the national standard specifications issued by the Ministry of Industry.